Pengaruh BAP (Benzyl Amino Purine) Pada Pertumbuhan Brokoli Hibrida (Brassica oleracea Var. Valencia) Dan Kandungan Sulforafan Pada Kultur In vitro - Dewi Chintya Tompo; Wenny Tilaar; Edy Fredy Lengkong (AGRI-SOSIOEKONOMI, 2022)
This study aimed to determine the effect of BAP on the growth of hybrid broccoli and the synthesis of sulforaphane content grown on MS media. Observations were made for 2 weeks, namely on the first day after planting until the 14th day after planting. This study used a completely randomized design with 4 treatments and was repeated 9 times. The results showed that on the first day after planting the hybrid broccoli had germinated. It was found that the highest Broccoli sprout height in the treatment without BAP (Control) was 8.82cm, the highest weight of Broccoli sprouts in the treatment without BAP (Control) was 0.17g, and the highest sulforaphane content in the 1 ppm BAP treatment was 6.56µg/g.